Pengaruh Model Teams Games Tournament (TGT) Berbantuan Wordwall (Gameshow Quiz) terhadap Keterampilan Berpikir Kritis dan Hasil Belajar Siswa SMAN 14 Samarinda - Mudzalifah, Rizky; Herliani, Herliani; Akhmad, Akhmad; Jailani, Jailani (Biocaster : Jurnal Kajian Biologi, 2025)
The purpose of this study was to evaluate the effectiveness of the Teams Games Tournament (TGT) learning model based on Wordwall type Gameshow Quiz in improving learning outcomes and critical thinking skills of class XI students at SMAN 14 Samarinda. This study used a Quasi-Experimental design with a Non-Equivalent Control Group Design. and Purposive Sampling techniques in sample selection, and T-Test and N-Gain tests to analyze the results. The results showed that the N-Gain of critical thinking skills in the experimental group was 0.53 (moderate category) and in the control group was 0.32 (moderate category). On the other hand, the N-Gain for learning outcomes in the experimental group was 0.56 (moderate category), while in the control group it was 0.25 (low category). The results of the hypothesis test analysis, critical thinking skills and learning outcomes each had significant values ​​of 0.002 and 0.000. Thus, the TGT model with Wordwall Gameshow Quiz media is effective in improving critical thinking skills and learning outcomes of class XI students at SMAN 14 Samarinda.